Exploring the potential of curcumin-loaded PLGA nanoparticles for angiogenesis and antioxidant proficiency in zebrafish embryo (Danio rerio) - Achinta Singha; Mave Harshitha; Krithika Kalladka; Gunimala Chakraborty; Biswajit Maiti; Akshath Uchangi Satyaprasad; Anirban Chakraborty; Samir Kumar Sil (SpringerOpen, 2024)
Abstract Background Curcumin is an age old traditional medicine. Although curcumin has several advantages, its water solubility and bioavailability limit its use as a natural therapeutic agent. Polymeric nano curcumin could be an excellent option to overcome these challenges to augment its therapeutic efficacy. This work aimed to synthesize curcumin-loaded PLGA nanoparticles and assess their angiogenic and antioxidant potential in the zebrafish model. Results The double emulsion solvent evaporation process was employed to make curcumin-loaded PLGA nanoparticles. Curcumin showed ~ 28.23 (± 2.49) encapsulation efficacy with an average diameter of PLGA nanoparticles 168.5 (± 2.5) nm and curcumin nanoparticles about 281.6 (± 17.2) nm, respectively. The curcumin nanoparticles showed no developmental toxicity to the zebrafish embryos while reduced toxicity compared to the native curcumin. Further, the curcumin nanoparticles reduced the generation of reactive oxygen species and improved angiogenesis in the model system. All these results confirmed that the nanoparticle has had higher bio-efficacy than that of native curcumin. Conclusion This study shows that PLGA curcumin nanoparticles hold an excellent therapeutic promise for wound healing, tissue regeneration and other biomedical applications where angiogenesis and ROS play critical role.